Methanol adsorption-oxidation over V2O5 - A mass spectrometry study - Gambaro, Luis Alberto (2004)
The methanol adsorption-oxidation over V2O5 (transient study) was monitored by mass spectrometry (MS) of desorbed molecules produced over the catalyst by reactive interaction at 40, 100 and 150°C. Then, temperature programmed desorption (TPD) tests were conducted to analyze the products again by MS. Conclusions drawn from study were that methanol molecules replace some of the water molecules adsorbed onto the V 2O5, interact with those exhibiting higher adsorption energy and may suggest that methanol is linked to the solid through water molecules. By TPD, only the following products were identified: different amounts of water, formaldehyde, CO and, at low temperature, methanol. For those temperatures, V2O5 shows only redox properties since neither condensation products nor CO2 were encountered.